2019
DOI: 10.1039/c9sc01229j
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric metallomesogens composed of achiral spin crossover molecules

Abstract: We report for the first time ferroelectricity induced by spin transition associated with a crystal – liquid crystal phase transition in achiral spin crossover molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
(28 reference statements)
2
26
0
Order By: Relevance
“…The molecular length calculated by the time‐dependent density functional theory (TD‐DFT) for Pt‐L 1 16 is 29 Å (Supporting Information, Figure S10), which is commensurate with that estimated from X‐ray diffraction (28.8 Å), indicating that the mesophases belong to a non‐tilted lamellar phase. Combined with the characteristics of three high‐order diffraction peaks in a small‐angle range, we assume that there are intercalated structures in LCs phase [46–48] . Two molecules pack antiparallelly to form a tail‐to‐tail dimer, the rigid metalloaromatic units form the layers and the peripheral phenoxyalkyl chains are disorderly distributed between the layers.…”
Section: Figurementioning
confidence: 99%
“…The molecular length calculated by the time‐dependent density functional theory (TD‐DFT) for Pt‐L 1 16 is 29 Å (Supporting Information, Figure S10), which is commensurate with that estimated from X‐ray diffraction (28.8 Å), indicating that the mesophases belong to a non‐tilted lamellar phase. Combined with the characteristics of three high‐order diffraction peaks in a small‐angle range, we assume that there are intercalated structures in LCs phase [46–48] . Two molecules pack antiparallelly to form a tail‐to‐tail dimer, the rigid metalloaromatic units form the layers and the peripheral phenoxyalkyl chains are disorderly distributed between the layers.…”
Section: Figurementioning
confidence: 99%
“…Magnetic switching accompanied by nonpolar-polar structural transition has been observed for several compounds. 28,29,34,54,55 However, ferroelectricity accompanied by magnetic switching in a single-phase molecular material remains to be demonstrated. In the compound prepared in this study, the ferroelectric phase transition as actuated by the motion of sulfate anions is due to a minute structural change in the Co(II) complex cations.…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…Consequently, the development of molecular materials that exhibit correlated magnetic switching and ferroelectric properties is highly desired. [28][29][30][31][32][33][34] Our previous study on single-crystal [Co II (en) 3 ](ox) (en = ethylenediamine; ox 2− = oxalate dianions) revealed that the unquenched orbital angular momentum of [Co II (en) 3 ] 2+ cations is highly susceptible to minor changes in coordination configuration. 35 In this compound, the order-disorder phase transition of ox 2− dianions in cavities encapsulated by five complex cations is reminiscent of the perovskite compounds that exhibit ferroelectric properties, which are derived from the polarization of dynamic molecular cations in their frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular functional materials exhibiting both SCO behavior and ferroelectric property are of significant interest because of the potential that resulting magnetoelectric (ME) effects might be anticipated. However, to the best of our knowledge, there is a general lack of reports concerned with the synthesis and investigation of such ferroelectric SCO compounds [4f, 8] . Recently in a solid‐state SCO ferroelectric study it was shown that a hydrated iron(II) complex of type [Fe(bpp) 2 ](isonic) 2 ⋅2H 2 O (bpp=2,6‐bis‐(pyrazol‐3‐yl)pyridine; isonic=isonicotinate) was driven by structural transformation from a non‐polar to polar space group through the removal of water [8] .…”
Section: Methodsmentioning
confidence: 99%